Student’s Logical Reasoning Ability in Terms of Sequential Thinking Style - Andini Siwi Pamungkas; Masduki Masduki (Kreano: Jurnal Matematika Kreatif-Inovatif, 2022)
Logical reasoning ability plays an important role in serving students to understand and solves mathematical problems. The students' thinking style is one of the factors that affect the way students solve problems. This study aims to reveal the student's logical reasoning ability based on a sequential thinking style. This research used a qualitative approach with a case study design. The subjects of this study included 15 grade 8 students due to limited access during the Covid-19 pandemic. We used Gregorc's thinking style questionnaire to map students' thinking styles and three straight-line equation questions to measure students' logical reasoning abilities. Four students, two students for concrete and abstract sequential thinking styles respectively, were interviewed to further revealed their logical thinking abilities. The results showed that there were differences in students' logical thinking abilities based on differences in thinking styles on indicators of constructing and establishing assumptions, assessing and testing, establishing generalizations, and determining conclusions. Thus, it can be concluded the thinking style can affect the students' logical thinking abilities.